PENGARUH BEBAN KERJA DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN PADA CV MARVELLA DIGITAL COPY & PRINTING - Ni Wayan Candra Dewi; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Marvella Digital Copy & Printing is a private company engaged in printing and retail of school and office stationery. On CV. Marvella Digital Copy & Printing is a phenomenon where employees stop or resign every year, mostly because employees feel less able to meet the demands of work and the second gets a job in another place or company. As well as the phenomenon of the job order system in the printing section of the CV. Marvella Digital Copy & Printing, which is when there is an order in a large capacity or an order that comes almost at the same time the employees experience being overwhelmed in preparing the customer's ordered goods. This study aims to examine and obtain empirical evidence of the effect of workload and job satisfaction on employee turnover intention at CV Marvella Digital Copy & Printing. The population in this study were all employees of CV. Marvella Digital Copy & Printing as many as 37 people. Determination of the sample using the census method or saturated sample. The analytical tool used is multiple linear regression analysis, classical assumption test, F test, t test. he results of this study indicate that workload has a positive & significant effect on employee turnover intention at CV Marvella Digital Copy & Printing. Job satisfaction has a negative & significant effect on turnover intention in CV. Marvella Digital Copy & Printing. It is recommended to CV Marvella Digital Copy & Printing to provide support and motivation and give awards to employees so that they feel valued and enthusiastic about their work and emphasize to each employee to always help each other in completing work, so that the work environment becomes more comfortable and full of family. This study also has limitations, namely the independent variables used in this study do not cover all the factors that influence employee turnover intention at CV Marvella Digital Copy & Printing.